In memoriam: Rashad Sami Barsoum - Naicker, Saraladevi; Hafez, Mohamed Hany; Dirks, John H (African Journal of Nephrology, 2023)
Rashad Sami Barsoum, a pioneer in nephrology in Egypt and Africa, and former secretary general of the International Society of Nephrology and inaugural past president of the African Association of Nephrology, died on 25 October 2022, at the age of 81.